Effects of geographical and dietary variation on the symbiotic flagellate protists communities of the subterranean termite Reticulitermes grassei Clément - Duarte, S. (2015)
Despite their importance on diverse ecosystems, termites may also be considered severe pests of wood in service, and also as agricultural and forestry pests. Subterranean termites’ ability to digest lignocellulose relies not only on their digestive tract physiology, but also on the symbiotic relationships established with flagellate protists and bacteria. In this tripartite lignocellulolytic system, the termite contribute with endogenous cellulases and mechanical processing, flagellate protists phagocyte the wood particles and digest them, and prokaryotes have, among others, an important role in maintaining the physical-chemical equilibrium inside the termite hindgut. The flagellate protist community living inside the termites is rather diverse, as there is a strong division of labour among them to accomplish the intricate process of lignocellulose digestion. The objectives of this work were to: 1) investigate the changes in flagellate protists communities of the termite Reticulitermes grassei in different locations; 2) test the possible effect of different laboratorial diets on diversity and abundance of the flagellate protists. R. grassei termites were captured in four different locations (Évora, Faial Island, Leiria and Sesimbra), in Portugal, and their symbiotic flagellate protist community diversity and abundance was evaluated. Termites belonging to the same colony were submitted to six different diets (natural diet, pine wood, European beech, thermally modified beech, cellulose and starvation) and after the trials their flagellate protist community was also evaluated. The differences between termite colonies from different locations may not be denied, although not considered to be significant. Similar flagellate protists communities were found on non-treated sound woods, while cellulose fed and starving termites had significantly different communities. The flagellate protists community of untreated beech and thermally modified beech fed termites were considered to be significantly different, with three morphotypes missing in the treated wood fed termites. Although the effects of geographical location were not considered significant, the laboratory diets caused major adaptations of the flagellate protists communities. The termite symbiotic flagellate protists community is a dynamic assemblage able to adapt to different conditions and diets.